Autophagic death of neural stem cells mediates chronic stress-induced decline of adult hippocampal neurogenesis and cognitive deficits. Issue 3 (3rd March 2020) - Jung, Seonghee; Choe, Seongwon; Woo, Hanwoong; Jeong, Hyeonjeong; An, Hyun-Kyu; Moon, Hyewon; Ryu, Hye Young; Yeo, Bo Kyoung; Lee, Ye Won; Choi, Hyosun; Mun, Ji Young; Sun, Woong; et al.
ABSTRACT: Macroautophagy/autophagy is generally regarded as a cytoprotective mechanism, and it remains a matter of controversy whether autophagy can cause cell death in mammals. Here, we show that chronic restraint stress suppresses adult hippocampal neurogenesis in mice by inducing autophagic cell death (ACD) of hippocampal neural stem cells (NSCs). We generated NSC-specific, inducible Atg7 conditional knockout mice and found that they had an intact number of NSCs and neurogenesis level under chronic restraint stress and were resilient to stress- or corticosterone-induced cognitive and mood deficits. Corticosterone treatment of adult hippocampal NSC cultures induced ACD via SGK3 (serum/glucocorticoid regulated kinase 3) without signs of apoptosis. Our results demonstrate that ACD is biologically important in a mammalian system in vivo and would be an attractive target for therapeutic intervention for psychological stress-induced disorders. Abbreviations: AAV: adeno-associated virus; ACD: autophagic cell death; ACTB: actin, beta; Atg: autophagy-related; ASCL1/MASH1: achaete-scute family bHLH transcription factor 1; BafA1 : bafilomycin A1 ; BrdU: Bromodeoxyuridine/5-bromo-2ʹ-deoxyuridine; CASP3: caspase 3; cKO: conditional knockout; CLEM: correlative light and electron microscopy; CORT: corticosterone; CRS: chronic restraint stress; DAB: 3, 3ʹ–diaminobenzidine; DCX: doublecortin; DG: dentate gyrus; GC: glucocorticoid; GFAP: glial fibrillary acidic protein; HCN: hippocampal neural stem; i.p.: intraperitoneal; MAP1LC3B: microtubule-associated protein 1 light chain 3 beta; MKI67/Ki67: antigen identified by monoclonal antibody Ki 67; MWM: Morris water maze; Nec-1: necrostatin-1; NES: nestin; NR3C1/GR: nuclear receptor subfamily 3, group C, member 1; NSC: neural stem cell; PCD: programmed cell death; PFA: paraformaldehyde; PX: Phox homology; PtdIns3P: phosphatidylinositol-3-phosphate; RBFOX3/NeuN: RNA binding protein, fox-1 homolog (C. elegans) 3; SGK: serum/glucocorticoid-regulated kinases; SGZ: subgranular zone; SOX2: SRY (sex determining region Y)-box 2; SQSTM1: sequestosome 1; STS: staurosporine; TAM: tamoxifen; Ulk1: unc-51 like kinase 1; TUNEL: terminal deoxynucleotidyl transferase dUTP nick end labeling; VIM: vimentin; WT: wild type; ZFYVE1: zinc finger, FYVE domain containing 1; Z-VAD/Z-VAD-FMK: pan-caspase inhibitor